The Influence of Low Temperature on the Scots Pine Callus Culture - Korotaeva N.Е.; Shmakov V.N.; Pyatrikas D.V. (Journal of Stress Physiology & Biochemistry)
The method of callus culture is a convenient tool for assessing of intracellular changes occurring in response to adverse effects, which reduces the experimental time and laboratory resources. Factors of intracellular resistance of coniferous trees to low positive temperatures have not been studied enough. The study of the sustainability mechanisms of the economically important species and forest-forming tree species, Scots pine, is relevant for the research region. The objective of the research was to assess the suitability of callus culture obtained from Scots pine (Pinus sylvestris L.) buds for studying the factors of bud cell resistance to low positive temperatures. Callus cultures obtained on bud explants were exposed to +4 or +1 °C for 7 days, after which the growth rate of the cultures, cell viability, and oxidative stress indicators (the content of hydrogen peroxide and superoxide anion; the activity of peroxidase and lipid peroxidation) were assessed. Before the exposure, callus cultures differed in growth rate, viability and in the development of oxidative stress, which is probably due to the genetic differences in the trees from which the buds were obtained, and is consistent with the data of other studies. Low positive temperatures suppress the growth of cultures, which indicates the restructuring of cell metabolism in the direction of protective activity. After exposure to low positive temperatures, all cultures were characterized by an increase in lipid peroxidation activity, indicating the development of oxidative stress. The absence of negative changes in cell viability and of an increasing in the content of hydrogen peroxide in all studied cultures indicates the ability of cells to withstand unfavorable changes. An increase in peroxidase activity found in all cultures indicates the activation of protective mechanisms. An increase in the content of superoxide anion may indicate the development of protective signaling. The study showed the ability of pine bud callus culture cells to withstand the used cold exposure, which makes the callus culture at researched conditions a useful test system for studying the mechanisms of cold resistance of Scots pine buds.